Properties of Sustainable Composite Construction Materials Derived from Recycled Polymers and Nanofillers - Al-Dikheeli, Mohammed Riyadh (Journal of Research Updates in Polymer Science, 2025)
This paper presents the investigation of sustainable construction composites manufactured from rPET and rHDPE with the addition of nano-silica, graphene oxide, and nanoclay. The composites were fabricated by melt blending and compression molding. Mechanical, thermal, and durability performances of the composites were tested according to ASTM specifications. Experimental test results revealed that with an optimum loading of 3 wt% nanofillers, there is an enhancement in tensile and flexural strength by up to 35%, improvement of thermal stability by 20-25 °C, and a reduction of water absorption by about 25% compared to unreinforced polymers. SEM, FTIR, and XRD analyses confirm enhancement in interfacial bonding and refinement of microstructure. Compressive strength in the range of 38 to 43 MPa was obtained, which indicates that these materials are suitable for lightweight panels and non-structural elements. The results are in agreement with previously reported literature data and emphasize the possibility of recycled polymer-nanofiller composites to provide low-density durable construction material with an environmental benefit. The engineering-oriented outcome of this study focuses on the optimization of filler dispersion and performance to enable scalable and sustainable application.